Lymphatic Disorders in Patients With Single Ventricle Heart Disease - Dori, Yoav; Smith, Christopher L. (Frontiers in Pediatrics, 2022)
Lymphatic abnormalities in patients with single ventricle physiology can lead to early Fontan failure and severe Fontan complications such as protein losing enteropathy (PLE), plastic bronchitis (PB), chylothorax, and edema. Recent developments in lymphatic imaging and interventions have shed new light on the lymphatic dysfunction in this patient population and the role of the lymphatic circulation in PLE, PB, and chylothorax. Here we review some of the latest developments in this field and discuss new treatment options for these patients.